Analysis of human resource management for teaching staff at Budi Murni 2 private elementary school in Medan - Regina Sipayung; Antonius Remigius Abi; Darinda Sofia Tanjung; Irmina Pinem (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study aims to analyze the human resource (HR) management of teaching staff at Budi Murni 2 Private Elementary School in Medan, focusing on teacher needs planning, recruitment, training and development, performance evaluation, and the challenges the school faces in managing its teaching staff. The research method used is a descriptive qualitative approach, employing data collection techniques such as interviews, observations, and documentation. The results indicate that HR management at this school has been conducted systematically, with planning tailored to the school's needs, and continuous improvements in recruitment, training, and performance evaluation processes. This study makes an important contribution by highlighting the need for human resource planning based on real needs at the elementary school level and by introducing the concept of competency-based evaluation to improve educators' performance. The recommendations provided include enhancing continuous teacher training, strengthening competency-based evaluation, and reinforcing the principal's role in managing human resources more effectively. It is hoped that the results of this study will provide a foundation for the development of more effective and integrated human resource management for educators, as well as serve as a reference for other elementary schools in this area, grounded in real needs and more objective measurements.